“What Do We Do With all This Dying?” : South African Time, Space, and Place in Forensic Evidence - Robyn Gill-Leslie (International Journal for Crime, Justice and Social Democracy)
Forensic investigations during truth recovery after atrocity often apply rights-based, socio-cultural approaches to dead and missing bodies. This article suggests focusing on universal “rights”, such as the right to dignity in death and the right to know what happened to family members, can occlude forensic understandings stemming from local knowledge systems. Deploying the theoretical gesture of ukwakumkanya through the framing of transcorporeality, this article examines aspects of medico-legal evidence stemming from the Marikana Commission of Inquiry in South Africa—a commission established in the wake of the 2012 Marikana massacre. This article deepens discussion around how forensic information in truth recovery processes reflects not only social contexts, or opportunities to challenge state monopolies on forensic expertise, but also surfaces local understandings of time, space, and place. These offer new temporal, ecological, and relational interpretations of forensic output during truth recovery.